2020
DOI: 10.1002/pat.5107
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of fluorosilicone rubber containing perfluorocyclobutyl aryl ether

Abstract: A new curing system for high temperature vulcanized fluorosilicone rubber was studied by thermal cycloaddition reaction of trifluoroethylene aryl ether (TFVE). Fluorosilicone rubber containing perfluorocyclobutyl aryl ether (Si‐PFCB) was prepared by using the polysiloxane containing trifluorovinyl aryl ether (Si‐TFVE) as base gum. The basic formula of vulcanized rubber was determined as: 100 parts Si‐TFVE (0.10%TFVE, mol), 50 parts fumed silica. The curing process is as follows: the primary curing process is 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The high-temperature resistance of silicone rubber can be enhanced by several methods: one is to modify its molecular main chain and side chain; the second is to select the appropriate crosslinking agent to enhance the stability of the crosslinking bond; the third is to add high-temperature-resistant additives. Some other methods such as purification, the surface treatment of fillers, and the combination of rubber materials also help to improve its high-temperature resistance [43][44][45][46][47][48]. Lai Liangqing et al found that phenyl ether silicone rubber had better air-heat-aging resistance than phenyl silicone rubber.…”
Section: Silicone Rubbermentioning
confidence: 99%
“…The high-temperature resistance of silicone rubber can be enhanced by several methods: one is to modify its molecular main chain and side chain; the second is to select the appropriate crosslinking agent to enhance the stability of the crosslinking bond; the third is to add high-temperature-resistant additives. Some other methods such as purification, the surface treatment of fillers, and the combination of rubber materials also help to improve its high-temperature resistance [43][44][45][46][47][48]. Lai Liangqing et al found that phenyl ether silicone rubber had better air-heat-aging resistance than phenyl silicone rubber.…”
Section: Silicone Rubbermentioning
confidence: 99%
“…In our previous work [13][14][15] , we reported two kinds of uorosilicone rubber containing per uorocyclobutyl aryl ether (PFCBAE) group. Fluorosilicone rubber containing PFCBAE was rst vulcanized by the thermal cyclization reaction of tri uoroethylene aryl ether (TFVE) which was also a new vulcanization method.…”
Section: Introductionmentioning
confidence: 99%
“…Conductive porous polymer foam materials have been invented as smart sensors based on the synergetic advantages of conductive materials and polymer foams, i.e., high conductivity, elastic conductive network, mechanical durability, as well as chemical modifiability. In particular, polydimethylsiloxane (PDMS) foam materials with high Si–O–Si bonding energy as the matrix to fabricate multifunctional sensors have shown explosive growth in the recent decade because of their chemical resistance, nontoxicity, wide-temperature stability, and thermal insulating properties. , Unfortunately, the low polarity of –CH 3 pendant moieties and similar solubility parameter (δ = 7.3 cal 1/2 cm –3/2 ) of PDMS foam materials with nonpolar organic solvents such as hexane (δ = 7.2 cal 1/2 cm –3/2 ) indicate that PDMS-based sensors would swell upon exposure to most nonpolar or low-polar solvents and oil, resulting in the severe deformation of foam structure and the failure of sensing performance. , Several chemical strategies, including the surface modification of silanes and intrinsic grafting with fluorine-containing groups on the Si–O–Si main chains, can be used to develop chemical resistant PDMS foam materials. For example, a n -octyltriethoxysilane-functionalized graphene oxide wide ribbon (GOWR) coated melamine foam (M-GOWR@MF) was designed based on interactions among them and showed excellent chemical robustness after exposure to different aqueous solutions (pH = 1, 7, and 14) . A room-temperature curable fluorosilicone elastomer with high 3,3,3-trifluoropropyl content on the main chains was synthesized by the anionic ring-opening polymerization route and possessed excellent resistance to corrosive acids and nonpolar hydrocarbon solvents .…”
Section: Introductionmentioning
confidence: 99%